Dahsyatnya sebuah Pelabelan - Junaidi (Wahdatul Ulum Institute, 2022)
Ages 7 to 13 years of age to seek an identity. all information received by the students related to him will serve as a reference to judge him. therefore let us always give a positive label on them.